Un ruolo di supplenza. L’associazionismo cattolico e l’accoglienza degli immigrati stranieri in Italia (1979-1986) - Possieri, Andrea (Disuguaglianza e generazioni in Italia 1914-2008, 2026)
This article reconstructs the role played by Catholic associations in welcoming migrants between 1979 and 1986. Three decisive moments stand out in this historical period. First, between 1978 and 1981, the first major mobilization in favor of refugees during the humanitarian crisis of the Vietnamese boat people. Second, in the early 1980s, there was a campaign to raise public awareness of the rights of foreign workers and their integration into Italian society. Finally, the establishment of the «Comitato per una legge giusta» which led to the approval of the first immigration law in Italy: the so-called Foschi Law of 1986.